Settlement of Conflicts of Values in the Area of Public Commercial Law . Comments in Relation to European Union Law - Długosz, Tomasz (Review of European and Comparative Law, 2023)
The author identifies two ways in which value conflicts can be solved in the area of public commercial law and proves that the method of weighing values and finding a compromise solution is predominant because of the strong politicization of public commercial law and the need to respond to dynamic changes in the economy. He also makes other suggestions on the values present in public commercial law and raises issues, among others, of Europeanisation of law and the impact of European Union law on the resolution of value conflicts, as well as the problems of economization of law and judicial review of decisions that are carried out in conditions of strong politicization.